1995
DOI: 10.1172/jci118308
|View full text |Cite
|
Sign up to set email alerts
|

Human and rat beta cells differ in glucose transporter but not in glucokinase gene expression.

Abstract: Glucose homeostasis is controlled by a glucose sensor in pancreatic fl-cells. Studies on rodent fl-cells have suggested a role for GLUT2 and glucokinase in this control function and in mechanisms leading to diabetes. Little direct evidence exists so far to implicate these two proteins in glucose recognition by human (3-cells. The present in vitro study investigates the role of glucose transport and phosphorylation in fl-cell preparations from nondiabetic human pancreata. Human fl-cells differ from rodent f8-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
199
1
4

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(214 citation statements)
references
References 42 publications
10
199
1
4
Order By: Relevance
“…Such glucose dependence is consistent with the fact that high K m GLUT2 is the dominating glucose transporter in rodent β-cells Johnson et al, 1990). It was therefore unexpected that human β-cells preferentially express low K m GLUT1 (De Vos et al, 1995), whose capacity is close to saturation already at threshold concentrations of glucose. However, consistent with the latter observation, transgenic re-expression of GLUT1 or GLUT2 into β-cells of GLUT2-null mice were equally efficient in restoring normal glucose sensing (Thorens et al, 2000).…”
Section: Role Of Metabolism For Glucose-induced Insulin Secretionsupporting
confidence: 74%
“…Such glucose dependence is consistent with the fact that high K m GLUT2 is the dominating glucose transporter in rodent β-cells Johnson et al, 1990). It was therefore unexpected that human β-cells preferentially express low K m GLUT1 (De Vos et al, 1995), whose capacity is close to saturation already at threshold concentrations of glucose. However, consistent with the latter observation, transgenic re-expression of GLUT1 or GLUT2 into β-cells of GLUT2-null mice were equally efficient in restoring normal glucose sensing (Thorens et al, 2000).…”
Section: Role Of Metabolism For Glucose-induced Insulin Secretionsupporting
confidence: 74%
“…In this context it is notable that some genes share high expression in beta cells and the liver and are involved in metabolic regulation such as GLUT1/2 and glucokinase [48]. The high abundance of CaM kinase IIb and d mRNA could lead to the conclusion that these isoforms are important molecules in beta-cell physiology, compared with CaM kinase IIg, but this has to be proven.…”
Section: Discussionmentioning
confidence: 99%
“…In endocrine pancreas ␤ cells, the predominant glucose-sensor has been definitively identified as glucokinase by knock out of the gene in mice (32,33), and the significance of the specific GLUT 2 expression in rodent ␤ cells is still disputed, especially as the amount of the GLUT 2 isoform seems to be very low in human ␤ cells (34,35). German (36) has shown that ␤ cells overexpressing GLUT 1 do not lose their ability to sense changes in glucose concentration within the physiological range and to respond by an appropriate stimulation of the insulin gene promoter.…”
Section: Discussionmentioning
confidence: 99%